Fulfillment Of Housing Infrastructure, Facilities And Utilities In Serdang Bedagai Regency - Christop HS. Pangaribuan; Abdi Sugiarto; Cut Nuraini (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Housing is a collection of houses in a housing area that are built in an organized manner complete with infrastructure, facilities and public utilities. As part of the organizational area, housing is one of the basic needs of society which is closely related to economic, socio-cultural, development and industrialization activities. Various housing problems that arise are characterized by the existence of slum organization areas in urban or rural areas, apart from population density which results in cramped and unhealthy environments, the large number of housing damaged due to natural disasters, the poor condition of building materials and limited infrastructure, public facilities and utilities. other. increase the number of uninhabitable houses. Fulfilling housing infrastructure, facilities and public utilities is one of the obligations of the Regional Government and housing developers as legal entities administering housing to prevent the increase in slum areas. Apart from creating livable houses, the aim of this research is to reveal the availability of housing infrastructure, facilities and public utilities referring to Serdang Bedagai Regency Regional Regulation Number 9 of 2021 concerning the Handover of Housing and Settlement Infrastructure, Facilities and Utilities. The research methodology used is qualitative and quantitative methods. Qualitatively, data was collected through interviewing related parties, such as local government, housing developers, local communities and direct observation. Quantitatively, data will be collected from the list of housing registered with the Licensing Service, the results of field surveys using questionnaires. The results obtained are the availability and obligation to deliver infrastructure, facilities and utilities in residential areas. Regarding standards for the provision of housing infrastructure, facilities and public utilities, the majority of housing does not yet meet the balanced housing category but is in accordance with the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 20/PRT/M/2019 concerning Ease and Assistance of Home Ownership for Low-Income People, apart from that, the quality of infrastructure, facilities and utilities are partly not maintained so they cannot be used optimally.